Foreign exchange market efficiency : Asia-Pacific focus / Wong Yuen Meng - Wong, Yuen Meng (2013)
The foreign exchange market is the largest financial market in the world. According to the Bank for International Settlements (BIS) 2010 Triennial Central Bank Survey, the annual turnover in the foreign exchange markets is estimated to be around USD1,000 trillion. Hence, a slight distortion in foreign exchange market efficiency represents a significant profit opportunity. From the review of market efficiency literature, it is found that the empirical evidence in respect of market efficiency has been mixed and inconclusive. In addition, there is also a serious neglect in the study of foreign exchange market efficiency especially in the Asia-Pacific region. This thesis investigates foreign exchange market efficiency using the Asia-Pacific currencies. We adopt the forward unbiasedness hypothesis and an event-study analysis in the investigation of the foreign exchange market efficiency. To the best of our knowledge, this is the first study which employs these two approaches jointly in a single research using the Asia-Pacific currencies as the core sample. This combination provides us with a more comprehensive view on the state of foreign exchange market efficiency. Ultimately, we find that the Asia-Pacific foreign exchange markets are generally efficient over the whole sample period but with some signs of market inefficiency only in some subsample periods in selective markets. It is also reported that the uncovered interest-rate parity generally holds true and hence the forward bias puzzle is further reinforced as a statistical artefact. The differences in the institutional characteristics such as a country’s income level and the extent of foreign exchange market liberalization causes heterogeneous results in the state of foreign exchange market efficiency over subsample periods. This thesis has discovered some evidence indicating that the Asian financial crisis (AFC) of 1997/98 is the more disturbing event as compared to the global financial crisis (GFC) 2008/09 in terms of impact on foreign exchange market efficiency in the Asia-Pacific. We have shown that the currencies managed under the free-float exchange rate regime as more resilient than those administered under the managed-float regime in the face of crisis. The empirical results have also confirmed that the exchange rates respond to both the United States and regional macroeconomic shocks. Finally, we have shown that those macroeconomic shocks related to the interest-rate announcements carry a larger impact to the exchange rates returns. Collectively, these findings bear several important implications for various stakeholders in the foreign exchange markets. It enables researchers to make a safe assumption of market efficiency in their future research work. For policymakers, they may want to take into account the resilience of free-float exchange regime in confronting a crisis when considering which regime to be adopted as the preferred currency management system. To market participants, they may have to be very cautious in applying a currency carry trade strategy, which aims to exploit the failure of the uncovered interest-rate parity, in the Asia-Pacific foreign exchange markets as the empirical results show that the parity condition generally holds true in the long run.